Near-Infrared Dual-Gas Sensor System for Methane and Ethane Detection Using a Compact Multipass Cell - Xi, Zhenhai; Zheng, Kaiyuan; Zheng, Chuantao; Zhang, Haipeng; Song, Fang; Li, Chunguang; Ye, Weilin; Zhang, Yu; Wang, Yiding; Tittel, Frank K. (Frontiers in Physics, 2022)
In this invited paper, a compact dense-pattern multipass cell-based near-infrared sensor system was demonstrated for detection of parts-per-billion in volume (ppbv)-level methane (CH4) and ethane (C2H6). The dimension size of the fabricated gas cell is 18.5×8×9 cm3 with an absorption path length of 9.39 m. CH4 measurement was realized within a spectral range of 6046–6048 cm-1 and an absorption line of 6046.95 cm-1. The spectral range for C2H6 detection is 5951–5953 cm-1 with an absorption line of 5951.73 cm-1. Allan deviation analysis was used for evaluating the dual-gas sensing performance, and a detection limit of 78 ppbv for CH4 and 190 ppbv for C2H6 were achieved, respectively, with an averaging time of 0.8 s. Furthermore, CH4 measurement in the indoor and outdoor atmosphere was both performed to verify the field sensing capability of the sensor system. Compared with two separate sensor systems for CH4/C2H6 sensing, the proposed dual-gas sensor system using two near-infrared lasers and one multipass cell has the advantages of low-cost, compact-size without decreasing the selectivity and sensitivity.